Novel drugs of abuse and bioanalytical strategies in Forensic Toxicology: metabolomics, analysis in blood, urine or DBS and human performance and post mortem cases - Campos, Eduardo Geraldo de (2020)
In recent years, the problem of drug abuse has become more complex with the emergence of new drugs, including new psychoactive substances (NPS). NPS are unknown substances, never reported before, or previously known substances that have been used in a different way. In addition to NPS, other new drugs of abuse have also emerged in forensic casework, such as 2,4- dinitrophenol (2,4-DNP), a weight loss agent illegally used that has caused many deaths and has no antidote. In this context, further studies and methods of toxicological analysis in biological fluids are required. Dried Blood Spots (DBS) have been proposed as a bioanalytical alternative for NPS determination based on application of a low volume of blood onto a paper card, reducing the volumes required for collection and extraction, making shipping easier, minimizing collection risks, and not decreasing the stability of many drugs. Another analytical approach adopted in the study of NPS is the combination of human liver microsome incubations and high resolution mass spectrometry (HRMS) for structural elucidation of potential metabolites of new drugs. Thus, the aims of this work were: (I) the development and validation of methods for NPS analysis in DBS via gas chromatography-mass spectrometry (GC-MS) or ultra-high pressure liquid chromatography tandem mass spectrometry LC-MS/MS; (II) the development of validation methods for the analysis of 2,4-DNP in blood and urine via GC-MS; and (III) in vitro metabolism studies of NPS via incubation with human liver microsomes and HRMS. As results, an alternative method was developed for the preparation of DBS, using a salt tablet for replacing the paper, for the analysis of cocaine, methamphetamine and MDMA via GC-MS, and ultrasound-assisted derivatization. However, the method is sensitive only to high concentrations of these drugs in saltsupported DBS.The ultra-high pressure liquid chromatography quadrupole time of flight mass spectrometry (UPLC-QTOF-MS) screening method for classic abuse drugs and NPS had detection limits of 0.5 to 20 ng/mL, with recoveries greater than 70% (except for alpha-PVP, LSD, heroin and mitragynine). The investigated drugs were stable for up to 37 days in DBS at - 20oC, except mytraginine. At room temperature, most compounds were stable in DBS except 4- fluoro-amphetamine, acrylfentanyl, heroin, mephedrone, methylone, N-ethyl-hexedrone, pentylone, alpha-PVP and N-ethyl-pentylone. Good correlation was observed between results obtained in the analysis of authentic liquid blood samples and DBS. Good results were also obtained with the synthetic cannabinoid screening method in DBS, with detection limits between 0.5 and 2 ng/mL using UPLC-MS/MS and high stability after 20 days at room temperature or at -20oC. The confirmatory method for analysis of synthetic cathinones in DBS also yielded good results, with R2 greater than 0.99, accuracy between 4.43% - 20.0%, intra-assay precision between 5.44% - 13.3% and inter-assay precision between 9.44% - 16.1. In in vitro metabolism studies, eight, three, five, five and six Phase I metabolites were identified and characterized for 4- methyldiethcathinone (4-MDEC), 3,4-dichloroethcathinone (3,4-DCEC), tertylone, Nethylhexedrone and N-ethylhexylone, respectively. The method of analysis of 2,4-DNP also showed satisfactory results of linearity, inter-assay inaccuracy (less than 10.6%), intra-assay inaccuracy (less than 10.7%) and 92.1% recovery. Three human intoxication cases were positive, with concentrations in the range of 61.6 - 220 mg/L in urine and <3 - 114 mg / L in blood. By performing this study, it was possible to use modern methods for the analysis/study of NPS and / or traditional illicit drugs, with implications and potential for application in routine forensic analyzes.